Analisis Usabilitas Pengguna E-learning Menggunakan HCI di SMKAl-Musyawirin - Kuju Susilawati; Nana Suarna; Dita Rizki Amalia (INTERNAL (Information System Journal), 2022)
Currently Al-Musyawirin Vocational School is implementing the web e-learning method by utilizing internet technology to attract students' interest in learning. However, the lack of student understanding in learning to use web e-learning and the unattractive e-learning design causes obstacles to online learning. Therefore, it is necessary to design an e-learning web learning system using HCI (Human Computer Interaction) so that it can be more optimal and not boring. The research method used for this research is the survey method from SUS consisting of 10 questions, each of which has 5 points with a Likert scale as a response. The results of this study obtained an SUS score of 77, which was obtained by the teacher and a score of 68.9 which was obtained by students at SMK Al-Musyawirin. On the Grade Scale, the two SUS scores can be seen to be in Grade C (okay) which indicates the score is classified as normal, neither above nor below the average.